Intramolecular hydrogen transfer reactions catalyzed by pentamethylcyclopentadienyl rhodium and cobalt olefin complexes: Mechanistic studies. (8th January 2016) - Bolig, Andrew D.; Lyons, Thomas W.; DiSalvo, Darren T.; Brookhart, Maurice
Graphical abstract: The mechanism of intramolecular transfer dehydrogenation catalyzed by [Cp ∗ M(VTMS)2 ] (M = Rh, Co, Cp ∗  = C5 Me5 ) complexes has been studied using vinyl silane protected alcohols as substrates. Using deuterium-labeled substrates, the regioselectivity of H/D transfers was investigated using NMR spectroscopy. These studies establish a regioselective pathway involving alkene directed α-C–H activation, 2, 1 alkene insertion, and finally β-hydride elimination to give silyl enol ether products. Abstract: The mechanism of intramolecular transfer dehydrogenation catalyzed by [Cp ∗ M(VTMS)2 ] (1, M = Rh, 2, M = Co, Cp ∗  = C5 Me5, VTMS = vinyltrimethylsilane) complexes has been studied using vinyl silane protected alcohols as substrates. Deuterium-labeled substrates have been synthesized and the regioselectivity of H/D transfers investigated using 1 H and 2 H NMR spectroscopy. The labeling studies establish a regioselective pathway consisting of alkene directed α C–H activation, 2, 1 alkene insertion, and finally β-hydride elimination to give silyl enol ether products.